Simple Self-Assessment Tool to Predict Osteoporosis in Taiwanese Men - Liu, Dung-Huan; Hsu, Chung-Yuan; Wu, Pei-Ching; Chen, Ying-Chou; Chen, You-Yin; Chen, Jia-Feng; Yu, Shan-Fu; Cheng, Tien-Tsai (Frontiers in Medicine, 2021)
Background Although self-assessment tools for predicting osteoporosis are convenient for clinicians, they are not commonly used among men. We developed the Male Osteoporosis Self-Assessment Tool for Taiwan (MOSTAi) to identify patients at risk of osteoporosis. Methods All participants completed a questionnaire on clinical risk factors for the fracture risk assessment tool. The risk index was calculated by the multivariate regression model through the item reduction method. The receiver operating characteristic curve was used to analyze its sensitivity and specificity, and MOSTAi was developed and validated. Results A total of 2,290 men participated in the bone mineral density survey. We chose a model that considered two variables (age and weight). The area under the curve (AUC) of the model was 0.700. The formula for the MOSTAi index is as follows: 0.3 x (weight in kilograms) - 0.1 x (years). We chose 11 as the appropriate cut-off value for the MOSTAi index to identify subjects at risk of osteoporosis. Conclusions MOSTAi is a simple, intuitive and country-specific tool that can predict the risk of osteoporosis in Taiwanese men. Due to different demographic characteristics, each region of the world can develop its own model to identify patients with osteoporosis more effectively.